Makna Perjuangan pada Lirik Nasyid 90 Langkah Karya Santri Gontor: Analisis Semiotika - Asep Ridwan Fauzi; Dadan Rusmana (FKIP, Universitas Lakidende Unaaha, 2022)
This study examines the meaning of struggle in the lyrics of Gontor’s nasheed 90 Langkah using Roland Barthes semiotics analysis. It focuses on denotation, connotation and myths meanings. The research method used is qualitative method, means data collection techniques with forms of analysis and conclusions. To collect data are used study of document, by searching data from various sources needed, and observational studies, by observing the object to be studied. The results of a semiotic study of the lyrics to the nasheed 90 Langkah are as follows. The denotation meaning of the lyrics of the nasheed 90 Langkah is the students struggle in seeking knowledge in Islamic School. The connotation meaning is the songwriter explained that this Islamic School that has been existing for 90 years can encourage the students to become the next leaders who possess the struggle, sincerity, humble and constancy values in their bocy and hearth. The myths meaning contained in the lyrics of this song is the songwriter wants to say that Islamic school is the place to make an innocent soul, the next leader who useful for the world.